Game Edukasi Berbasis Android Pengenalan Serangga Pada Anak Tunagrahita SLB Negeri Sukoharjo - Rama, Rama Elian Zuldi; Al Irsyadi, Fatah Yasin (Universitas Samudra, 2024)
Mental Retardation refers to individuals with below-average intellectual or mental limitations caused by abnormalities in the brain's structure or function. They have deficits in adaptive behaviors such as daily living skills, social skills, language, and communication. Special care and support, including special education, are needed to enhance their development and quality of life. SLB Negeri Sukoharjo in Central Java provides special education for individuals with Mental Retardation, teaching basic skills, social skills, and life skills for future independence. Observations and interviews reveal that SLB still uses conventional learning media, leading to issues like students folding, tearing, and discarding paper-based materials. To address this, the author develops educational games as interactive learning media to promote active student participation and make the learning process more engaging for Mental Retardation students. The game, Jelajah Serangga, is designed using Construct2 software and the Game Development Life Cycle (GDLC) research method. It achieves an excellent rating with an SUS score of 85, indicating high quality. This game effectively supports learning at Sukoharjo State Special School.